Sensitivity of loan size to lending rates: Evidence from Ghana's microfinance sector - Samuel Kobina Annim (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper examines the combined effect of interest rates and poverty levels of microfinance clients on loan size. Cross section data on 2,691 clients and non-clients households from Ghana is used to test the hypothesis of loan price inelasticity. Quantile regression and variants of least squares methods that explore endogeneity are employed. We find the expected inverse relationship only for the 20th to 40th quantile range. The semi-elasticity of loan amount responsiveness to a unit change in interest rate is more than proportionate and significant for the poorest group only. Market segmentation based on poverty level is suggested in targeting and sustaining microfinance clients.
Keywords: G20; G29; I30; 330; interest rate; sensitivity; loan; poor; microfinance; Ghana; Mikrofinanz; Armut; Kredit; Ghana